EFFECTIVENESS OF KATUK LEAVES ETHANOL EXTRACT TO AMOUNT OF OSTEOBLAST AND OSTEOCLAST IN ORTHODONTIC TREATMENT - Hillda Herawati; Fahrauk Faramayuda; Rudi Satria Darwis; Sarah Syarifah (Fakultas Kedokteran Gigi Unjani, 2021)
The optimal achievement of orthodontic treatment is determined by a bone remodelling process involving osteoblast, osteoclasts, and the estrogen hormone. Estrogen deficiency can increase osteoclast age and decrease osteoblast, resulting in an imbalance between osteoclasts and osteoblasts. One natural alternative that can replace the role of the hormone estrogen is phytoestrogens. Sauropus androgynus (L.) Merr (katuk) is a phytoestrogen that contains isoflavones with many similarities with estrogens. This research aims to determine the effectiveness of the various doses of ethanol extract of katuk leaves on the number of osteoblasts and osteoclasts. This research was conducted using experimental laboratory methods using 24 female Guinea pigs divided into a control group and three groups with various doses of 39.15 mg/BW, 78.3 mg/BW, and 156.5 mg/BW. The observations made in this test were the number of osteoblasts and osteoclasts on the alveolar guinea pig on day 14 and analysed using the one way ANOVA test (p <0.05). All guinea pigs have applied a rubber separator to the left incisor and given a dose according to the group, and after 14th days, histological preparations were made. The results showed that the highest number of osteoblasts was at a dose of 78.3 mg/BW, and the lowest number of osteoclasts was at a dose of 39.15 mg/BW with values of 15.03 ± 2.27 and 1.73 ± 0.56, respectively. Statistically, the number of osteoblasts between the treatment and control groups significantly differed (p = 0.04), while the number of osteoclasts between the treatment and control groups had no significant difference (p = 0.228). DOI : 10.54052/jhds.v1n1.p38-48